Social Networks among Indigenous Peoples in Mexico - Skoufias, Emmanuel; Lunde, Trine; Patrinos, Harry Anthony (2012)
This paper examines the extent to which social networks among indigenous peoples have a significant effect on a variety of human capital investment and economic activities, such as school attendance and work among teenage boys and girls, and migration, welfare participation, employment status, occupation and sector of employment among adult males and females. The analysis uses data from the 10 percent population sample of the 2000 Population and Housing Census of Mexico and an empirical strategy that allows taking into account the role of municipality and language group fixed effects. The authors confirm empirically that social network effects play an important role in the economic decisions of indigenous people, especially in rural areas. The analysis also provides evidence that better access to basic services, such as water and electricity, increases the size and strength of network effects in rural areas.